กระบวนการขับเคลื่อนความมั่นคงทางอาหารผ่านผักพื้นบ้าน จังหวัดในเขตภาคเหนือตอนบน - ประดิษฐ์สถาพร ชณิตา; มหาวรรณศรี ลออ; วงค์คินี วิไลพร; สุทธิ ประกายดาว (Area Based Development Research Journal, 2018)
This is a participatory action research. The objective was to examine the process that pushed forward food security through the cultivation and consumption of local vegetables. The research was conducted in two phrases. The first phrase focused on the situational assessment of food security at local and household levels in the upper northern provinces. The second phrase was on the study of development of a model for food security advancement through local vegetable cultivation in the pilot area. Sample of two phases, including chief executives of local administrative organizations, community leaders, knowledgeable local people, household members and organic farmers. Data collection tools were 1) food security questionnaires and Interview forms for community leaders, to gather the data related to policies, plans, and projects activities, which aimed to advance food security through local vegetable farming, 2) observation forms, 3) in-depth interview forms, and 4) focus group discussion form. The research tools were validated by three experts. The reliability of the questionnaires on food security was 0.83. The study found that only 44.1 percent of local administrative organizations in the upper northern provinces had put in place policies, plans, projects and activities related to community’s food security, which depended on the awareness of community leaders, the management, and the participation of people. Based on the analysis of the development of the model for food security advancement in the pilot area, it was found that the process comprised of sub-district development plans, enhancement of awareness about food security among organic farming members, utilization of the existing knowledge of groups of people, knowledge sharing, study visits, and initiation of community food stores which can be used as learning centers, thereby resulting in knowledge management on food security.